C-reactive protein-guided use of procalcitonin in COVID-19. Issue 4 (28th November 2021) - Houghton, Rebecca; Moore, Nathan; Williams, Rebecca; El-Bakri, Fatima; Peters, Jonathan; Mori, Matilde; Vernet, Gabrielle; Lynch, Jessica; Lewis, Henry; Tavener, Maryanna; Durham, Tom; Bowyer, Jack; et al.
Abstract: Background: A low procalcitonin (PCT) concentration facilitates exclusion of bacterial co-infections in COVID-19, but high costs associated with PCT measurements preclude universal adoption. Changes in inflammatory markers, including C-reactive protein (CRP), can be concordant, and predicting low PCT concentrations may avoid costs of redundant tests and support more cost-effective deployment of this diagnostic biomarker. Objectives: To explore whether, in COVID-19, low PCT values could be predicted by the presence of low CRP concentrations. Methods: Unselected cohort of 224 COVID-19 patients admitted to hospital that underwent daily PCT and CRP measurements as standard care. Both 0.25 ng/mL and 0.5 ng/mL were used as cut-offs for positive PCT test results. Geometric mean was used to define high and low CRP values at each timepoint assessed. Results: Admission PCT was <0.25 ng/mL in 160/224 (71.4%), 0.25–0.5 ng/mL in 27 (12.0%) and >0.5 ng/mL in 37 (16.5%). Elevated PCT was associated with increased risk of death ( P = 0.0004) and was more commonly associated with microbiological evidence of bacterial co-infection ( P < 0.0001). For high CRP values, significant heterogeneity in PCT measurements was observed, with maximal positive predictive value of 50% even for a PCT cut-off of 0.25 ng/mL. In contrast, low CRP was strongly predictive of low PCT concentrations, particularly <0.5 ng/mL, with a negative predictive value of 97.6% at time of hospital admission and 100% 48 hours into hospital stay. Conclusions: CRP-guided PCT testing algorithms can reduce unnecessary PCT measurement and costs, supporting antimicrobial stewardship strategies in COVID-19.